1940
DOI: 10.1021/j150403a004
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Alcohols. XXI. A Study of the Effect of the Anhydrides of Sorbitol on the Dissociation Constant of Boric Acid.

Abstract: In a previous communication (4) two of the authors (C. J. C. and J. C. K., Jr.) with Oakley studied the effect of the anhydrides of mannitol upon the dissociation constant of boric acid. Later the extraordinary potentiation of the dissociation constant of boric acid produced by a-mannitan was reported (1). Since sorbitan and isosorbide, the mono-and di-anhydrides, respectively, of sorbitol, were available for metabolic study, it was decided to determine the effect of these two compounds upon the titration curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…[7] Crystalline isosorbide was synthesized a few years later, [8] and evidence of its structure was published in 1946. [9] The difference between isosorbide in comparison to its two isomers isoidide and isomannide is the configuration of the two hydroxyl groups.…”
Section: General Facts and Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[7] Crystalline isosorbide was synthesized a few years later, [8] and evidence of its structure was published in 1946. [9] The difference between isosorbide in comparison to its two isomers isoidide and isomannide is the configuration of the two hydroxyl groups.…”
Section: General Facts and Propertiesmentioning
confidence: 99%
“…[36] In comparison to the conventional method using a homogeneous solution and heating for several hours, a highly efficient synthesis for C 8 -alkyl and different aromatic diethers of isosorbide with reaction times of only a few minutes and yields > 90 % has been achieved by using phase-transfer catalysis with microwave heating.…”
Section: Fuels Solvents and Plasticizersmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we describe the use of both dropin monomers obtained from renewable resources as well as the use of biobased alternatives to currently used raw materials in RMA binder resins. In Scheme 3, the main biobased raw materials featured in this study are shown: biobased diethyl malonate (Bio-DEM TM , used as a drop-in monomer to replace DEM prepared through the petrochemical process), isosorbide (1,4:3,6-dianhydro-D-glucitol) [6][7][8][9] and vegetable oils. Isosorbide is a commercially available, rigid bicyclic secondary diol produced starting from D-glucose.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1940s, the structures of isosorbide, isomannide and isoidide (i.e. the presence of the 1,4 and the 3,6 anhydro rings as well as the secondary OH-groups) were determined [9,10]. The importance of the DAHs has increased recently due to the stereoconfiguration of these materials, which gave some enhanced properties of synthesized polycondensates [11].…”
Section: Introductionmentioning
confidence: 99%